Accelerating Coronavirus Disease 2019 Therapeutic Interventions and Vaccines—Selecting Compounds for Clinical Evaluation in Coronavirus Disease 2019 Clinical Trials. Issue 11 (November 2021) - Buchman, Timothy G.; Draghia-Akli, Ruxandra; Adam, Stacey J.; Aggarwal, Neil R.; Fessel, Joshua P.; Higgs, Elizabeth S.; Menetski, Joseph P.; Read, Sarah W.; Hughes, Eric A.
Abstract : Given the urgent need for coronavirus disease 2019 therapeutics, early in the pandemic the Accelerating Coronavirus Disease 2019 Therapeutic Interventions and Vaccines (ACTIV) public-private partnership rapidly designed a unique therapeutic agent intake and assessment process for candidate treatments of coronavirus disease 2019. These treatments included antivirals, immune modulators, severe acute respiratory syndrome coronavirus 2 neutralizing antibodies, and organ-supportive treatments at both the preclinical and clinical stages of development. The ACTIV Therapeutics-Clinical Working Group Agent Prioritization subgroup established a uniform data collection process required to perform an assessment of any agent type using review criteria that were identified and differentially weighted for each agent class. The ACTIV Therapeutics-Clinical Working Group evaluated over 750 therapeutic agents with potential application for coronavirus disease 2019 and prioritized promising candidates for testing within the master protocols conducted by ACTIV. In addition, promising agents among preclinical candidates were selected by ACTIV to be matched with laboratories that could assist in executing rigorous preclinical studies. Between April 14, 2020, and May 31, 2021, the Agent Prioritization subgroup advanced 20 agents into the Accelerating Coronavirus Disease 2019 Therapeutic Interventions and Vaccines master protocols and matched 25 agents with laboratories to assist with preclinical testing. Abstract : Supplemental Digital Content is available in the text.